Coerências e ambivalências no ensino religioso escolar: um estudo do lugar do ensino religioso no projeto pedagógico de duas escolas distintas: Colégio Municipal Ana Elisa Lisboa Gregori e Colégio Franciscano São Miguel Arcanjo - Eleutério, Sidney Cristóvão (2012)
Abstract: This dissertation intends to explain the coherences and ambivalences on school Religious Education (RE) from a study of the place of religious education in the educational project of two distinct schools: the Municipal School Ana Elisa Lisbon Gregori and the Franciscan School St. Michael the Archangel. The research started from the conviction that, in its course through Brazilian territory, this curricular component is related to the space of political tensions, which involves negotiations between state and religions. In addition to the pedagogical questions, there are elements of legal, religious and epistemic order at stake. The main objective of the research was to analyze models and practices of religious education in these two schools, considering the presence in them of a plural religious public. It was considered their dilemmas and complexity from a threefold classification of Religious Educational models (Catechetical, Theological and Religious Sciences) present in theory and practice. The work was divided into three steps. Initially, it was shown how the Religious Education is present in the Brazilian Constitutions and on the educational legislation of the States of Sao Paulo and Rio de Janeiro, for later explaining of the present models at course in the Religious Education practice in Brazilian education. After, the field research made in the schools sought to identify the conflicts generated between students and teachers in the Religious Education classes, and tried to determine how the model of Sciences of Religion could set an important option in teacher training for the Religious Education, also being the one that can surpass with more gains the challenges of religious diversity among students. Finally, the main results of the survey were presented, which pointed to the need to have a greater clarity regarding the definition of the object of Religious Education and the contribution of Religious Science for this area of knowledge, since it will be necessary to rely always more, in the pedagogical plans of schools, with a religious multiplicity between students